On the path to net-zero: Establishing a multi-level system to support the complex endeavor of reaching national carbon neutrality - Köhnke, Fiona; Steuri, Bettina; El Zohbi, Juliane; Görl, Knut; Borchers, Malgorzata; Förster, Johannes; Thrän, Daniela; Mengis, Nadine; Oschlies, Andreas; Jacob, Daniela (Frontiers in Climate, 2023)
Limiting global warming to well below 2°C and pursuing efforts to limit it to 1.5°C, as agreed in the 2015 Paris Agreement, requires global carbon neutrality by mid-century at the latest. The corresponding carbon budget is decreasing steadily and significantly. To phase out carbon emissions in line with the specified temperature target, countries are formulating their mitigation efforts in their long-term low greenhouse gas emission development strategies (LT-LEDS). However, there are no standardized specifications for preparing these strategies, which is why the reports published to date differ widely in terms of structure and scope. To consider the multiple facets of reaching net-zero from a systemic perspective as comprehensively as possible, the authors propose the Net-Zero-2050 System: A novel, transferrable systems approach that supports the development of national endeavors toward carbon neutrality. The Net-Zero-2050 System is defined by three interconnected components: The Carbon-Emission-Based System, the surrounding Framing System and a set of system boundaries. For both systems levels, IPCC approaches were used as a basis and were then adjusted and supplemented by Net-Zero-2050. We suggest applying the Net-Zero-2050 System – beyond the project environment – in carbon emission based contexts at different levels. Especially at the national level, this would improve the comparability of the different national strategies to achieve carbon neutrality.